Ballistic Model of Two-Stage Light Gas Gun - Zbigniew SURMA (Problemy Mechatroniki)
A physical model and specificity of a two-stage light gas gun propulsion system are presented in this paper. For the considered system, a mathematical model of phenomena inside a combustion chamber, a light gas filled chamber, and a barrel was worked out. A numerical solution of the proposed model for the considered propulsion system gives pressures of powder gases, pressure of light gas, and motion parameters of a piston and a projectile. On the basis of the results of the accomplished calculations, influence of system structural parameters on the maximum pressure inside a compression chamber and a muzzle velocity of a projectile has been analysed. The final results of this work were used for development of the first in Poland a laboratory station with two-stage light gas gun intended for experimental investigation in the field of terminal ballistics of objects moving at hypersonic velocities.